Effectiveness of Behavioral Family Therapy in reducing depressive symptoms among older persons living with HIV/AIDS in Mbarara city, southwestern Uganda - Amanyire, Jordan Mutambi; Aheisibwe, Irene; Kaggwa, Mark Mohan; Rukundo, Godfrey Zari (International Journal of Scientific Research and Engineering Development, 2023)
Background: Behavioral Family Therapy (BFT) is a type of psychotherapy designed to identify family patterns that contribute to a behavioral disorder or mental illness and, helps family members to break habits. Studies in the developed world have reported BFT as an effective intervention in the management of depression, anxiety, psychosis, Alzheimer’s disease, learning disabilities and alcoholism. This intervention has not previously been used in Uganda. The current study aimed to assess the effectiveness of Behavioral Family Therapy in reducing depressive symptoms among older persons living with HIV/AIDS in Mbarara city, southwestern Uganda. This study was a follow up of a cross sectional study that was done among 265 older persons living with HIV/AIDS in Mbarara city where 22 patients (8.3%) had moderate- severe depression using PHQ 9 depression screening tool. Methods: The study design was Randomized Control Trial (RCT). Twenty-two participants with depression were randomly allocated to receive either BFT (intervention group) or routine care (comparison group). For those who received BFT, prior appointments with them were made, visited at their homes, convened family meetings, assessed their capacity to handle depression, shared more about depression, risk factors, copying strategies and other ways of handling depression. They were then followed up to assess progress on the goals made. For those who received routine care, they got routine medical services that included individual counseling, laboratory investigation and drugs. After 4 months, the patients on both groups were reassessed for depressive symptoms. Those who received BFT were reassessed at their homes while those of routine care were reassessed at their respective health facilities using PHQ-9 tool and thereafter, the findings were analyzed. The statistical methods used to investigate the statistical significance and practical significance were the t-test and effect sizes respectively. Thus, Impact measures/evaluation was based on differences of means using the test and practical significance was based on effect sizes (the Cohen’s d). Results: The results showed that the average depression scores in the Behavioral Family Therapy and routine care (control) groups differed at the stage of analysis by approximately 0.2 standard deviations. Cohen’s d indicate that the average depression scores differed by approximately 0.2 standard deviations with 95% confidence intervals of (0.64, 1.04). The confidence intervals for Cohen’s d include the null value of zero. Thus the behavioral family therapy had small effect but not statistically significant. Therefore, we cannot completely rule out the possibility that the behavioral family therapy had no effect on depressive symptoms. Therefore, we conclude that the intervention had a small impact but not statistically significant on reducing depressive symptoms among older patients with HIV/AIDS accessing care in selected health facilities in Mbarara City, southwestern Uganda. Conclusion: Behavioral family therapy (BFT) had a small effect on reducing the depressive symptoms among elderly HIV/AIDS patients but there is need to integrate behavioral family therapy in general management of patients with depression
Keywords: Behavioral Family Therapy; Depression; Older person